2014
DOI: 10.1111/fwb.12510
|View full text |Cite
|
Sign up to set email alerts
|

Native European eels as a potential biological control for invasive crayfish

Abstract: Summary Invasive species may have strong negative impacts on ecosystems. Invasive crayfish are well known to cause ecological imbalances in freshwater systems and have become targets in eradication programmes. The red swamp crayfish (Procambarus clarkii) is vulnerable to predation by several fish species. The European eel (Anguilla anguilla) appears to be a very good candidate given its benthic feeding activity and ability to recognise prey by odour. Our study took place from 2009 to 2013 in a closed system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The invasive crayfish can be considered to be forming a significant portion of the tigerfish diet due to its increasing frequency in the diet of tigerfish, as identified by stable isotopes. This is similar to a study by Aquiloni et al (2010) and Musseau et al (2015) who found that invasive crayfish was the most important prey of the European eel Anguilla anguilla. With the current study highlighting that every size-class of crayfish is being preyed upon, this might be used as a complement to the traditional trapping or eradication methods of invasive crayfish (see Aquiloni et al, 2010;Musseau et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The invasive crayfish can be considered to be forming a significant portion of the tigerfish diet due to its increasing frequency in the diet of tigerfish, as identified by stable isotopes. This is similar to a study by Aquiloni et al (2010) and Musseau et al (2015) who found that invasive crayfish was the most important prey of the European eel Anguilla anguilla. With the current study highlighting that every size-class of crayfish is being preyed upon, this might be used as a complement to the traditional trapping or eradication methods of invasive crayfish (see Aquiloni et al, 2010;Musseau et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to a study by Aquiloni et al (2010) and Musseau et al (2015) who found that invasive crayfish was the most important prey of the European eel Anguilla anguilla. With the current study highlighting that every size-class of crayfish is being preyed upon, this might be used as a complement to the traditional trapping or eradication methods of invasive crayfish (see Aquiloni et al, 2010;Musseau et al, 2015). Similar to our study, tigerfish can also be useful in controlling the population numbers of the redclaw crayfish.…”
Section: Discussionsupporting
confidence: 91%
“…Musseau et al . ). However, there are no reported large‐scale programmes of biocontrol that have successfully utilized piscivorous fish to suppress the invasion of a non‐native fish (Britton, Gozlan & Copp ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, sunfishes Lepomis spp. have been documented to regulate invasive rusty crayfish Orconectes rusticus in Wisconsin lakes (Roth et al 2007;Tetzlaff et al 2010), and European Eels Anguilla anguilla have similarly been successful at controlling invasive red swamp crayfish Procambarus clarkii in the Netherlands (Aquiloni et al 2010;Musseau et al 2015). Despite the prolific use of biological control agents, vertebrate species represent a small portion of all biological control targets (Saunders et al 2010;USDA 2013b).…”
mentioning
confidence: 99%